THE EFFECT OF PERSONAL ETHICAL PHILOSOPHY, INTERNAL LOCUS OF CONTROL AND ACADEMIC CULTURE ON PROFESSIONAL COMPETENCE OF ACCOUNTANT EDUCATORS IN PRIVATE UNIVERSITIES IN MAKASSAR - Syamsu Alam; Roslina Alam (JARES (Journal of Academic Research and Sciences), 2019)
This research aims at (1) exploring individual aspects of accountant educators in shaping professional accountants, and (2) situational aspects utilized by accountant educators as the media in shaping professional accountants in Makassar The independent variable of this research included Personal Ethical Philosophy, Internal Locus of Control, and Academic Culture, while the dependent variable was the Professional Competence of Accountant Educators (Y). The units of analysis, as well as the respondents, were 132 accountant educators in Makassar. To determine the sample, Simple Proportional Sampling with minimal respondent by Taro Yamane was utilized. Data analysis deployed multiple linear regression with error tolerance (α) of 5%. The result shows that Personal Ethical Philosophy significantly affected professional competence, with the t-calculated of 2.085. Internal Locus of Control also significantly affected professional competence, with the t-calculated of 2.158. Academic culture, with the t-calculated of 2.146, also significantly affected the professional competence of accountant educators.